Exploration and Valorization of Agri-Food Waste in A Circular Economy Ecosystem: Systematic Literature Review - Gesa Aldin Barqin; Nia Agustina (Journal Research of Social Science, Economics, and Management, 2026)
The exponential increase in global population triggers a surge in food demand that has a direct impact on the accumulation of waste in the agricultural and food industry sector (agri-food waste). Conventional disposal methods such as landfill and incineration have been shown to cause significant environmental degradation. This study used the Systematic Literature Review (SLR) method to integrate scientific evidence related to organic waste treatment strategies into high-value-added products (valorization) to support the transition to a zero-waste circular economy. Based on a comparative analysis of national and international literature, three main lines of valorization were found: (1) the transformation of agro-industrial waste (such as tofu pulp, straw, bran, and palm oil meal) and manufacturing defective food products into alternative feed for ruminant livestock, poultry, and fishery cultivation; (2) waste bioconversion using Black Soldier Fly (BSF) larval agents to produce animal proteins; and (3) thermochemical conversion through slow pyrolysis to produce high-performance active biochar for environmental remediation. The implementation of this technology in Indonesia still faces challenges in the form of regulatory ambiguity, variability in nutrient content, and contamination risk, which requires cross-sectoral policy synchronization to achieve the Sustainable Development Goals.